IMPLEMENTASI PENDIDIKAN AGAMA ISLAM SEKOLAH INDONESIA DEN HAAG - Ahmad Lutfi Haqi; Ahmad Fikri Haikal; Mualamatul Musawamah; Shoimmatun Nikmah; Lin Walidiya (IAIN Ambon, 2020)
Abstract: This journal discusses the implementation of Islamic education at the Elementary School level at the Indonesian School in The Hague. The background of this journal is the importance of Islamic Religious Education for elementary level students. This journal is intended to answer the problems of Islamic Education learning, the implementation of Islamic Education learning at SIDH. Data obtained by means of interviews or explanations of sources from SIDH online. The implementation of Islamic Education at Elementary School level at SIDH aims to improve the morals of students from an early age so that they become Muslim beings who can understand and practice the teachings of Islam in everyday life.. Keywords: SD (Elementari School), Islamic Education learning, learning implementation. Abstrak: Jurnal ini membahas tentang implementasi pendidikan Agama Islam jenjang SD di Sekolah Indonesia Den Haag. Latar belakang jurnal ini adalah pentingnya Pendidikan Agama Islam bagi peserta didik jenjang SD. Jurnal ini dimaksudkan untuk menjawab permasalahan pembelajaran PAI, implementasi pembelajaran PAI di SIDH. Data diperoleh dengan cara wawancara atau penjelasan narasumber dari SIDH secara daring. Implementasi Pendidikan Agama Islam jenjang SD di SIDH bertujuan memperbaiki akhlak peserta didik sejak dini agar mereka menjadi insan muslim yang dapat memahami dan mengamalkan ajaran Agama Islam dalam kehidupan sehari-hari. Keywords: SD (Sekolah Dasar), pembelajaran PAI, implementasi pembelajaran.